Species of the subgenus Chaetolabis, Townes 1945 of the genus Chironomus,Meigen 1803 (Diptera: Chironomidae), from a cytogenetic perspective - Martin, Jon (Zootaxa, 2014)
The polytene chromosomes of three North American species in the subgenus Chaetolabis of the genus Chironomus are described and compared to the published karyotypes of two Palearctic species. Chironomus (Chaetolabis) atroviridis has four polytene chromosomes, like the Palearctic C. globulus, while C. ochreatus and the North American populations of C. bitumineus each have three chromosomes due to tandem fusion of arm G to arm E, as in the Palearctic populations of C. bitumineus. The results support the existence of distinct species, particularly clarifying that the names C. atroviridis, C. bitumineus and C. ochreatus cannot be synonyms, as was suggested by some previous workers. The question of whether Lobochironomus "sp. Ya6" might be conspecific with C. macani is also discussed.